Methanol extraction residue of BCG in the treatment of transplanted rat tumours. - Hopper, D. G. (Nature Publishing Group, 1975)
Subcutaneous growth of immunogenic chemically induced rat sarcomata and a hepatoma was restricted when cells were injected into syngeneic animals in admixture with MER. Rats rejecting mixed inocula were immune to further challenge with the same tumour. Growth of a chemically induced mammary carcinoma which lacks detectable immunogenicity was suppressed when low cell inocula were injected in admixture with MER or intact BCG organisms, although animals were not immune to re-challenge. These studies indicate that clinically MER may be a suitable alternative to BCG for contact suppression of tumour growth or incorporation into tumour cell:adjuvant vaccines for active immunotherapy.